2018
DOI: 10.1038/s41598-018-28113-6
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of virtual reality based interventions for symptoms of anxiety and depression: A meta-analysis

Abstract: We report a meta-analysis of virtual reality (VR) interventions for anxiety and depression outcomes, as well as treatment attrition. We included randomized controlled trials comparing VR interventions, alone or in combination, to control conditions or other active psychological interventions. Effects sizes (Hedges’ g) for anxiety and depression outcomes, as post-test and follow-up, were pooled with a random-effects model. Drop-outs were compared using odds ratio (OR) with a Mantel-Haenszel model. We included 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
169
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(185 citation statements)
references
References 51 publications
7
169
2
7
Order By: Relevance
“…Effect sizes for PTSD symptom reduction in favour of VRET were medium (g = 0.62 for PTSD symptoms; g = 0.50 for depressive symptoms), and effects for treatment-related changes in anxiety symptoms were non-significant (g = 0.47, p = .387). These results are in line with previous research (Carl et al, 2019), but depict better outcomes than another meta-analysis (Fodor et al, 2018). Furthermore, our findings suggest that there is no significant difference between VRET and active controls regarding the improvement of PTSD symptoms (g = 0.25) and depressive symptoms (g = 0.24).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Effect sizes for PTSD symptom reduction in favour of VRET were medium (g = 0.62 for PTSD symptoms; g = 0.50 for depressive symptoms), and effects for treatment-related changes in anxiety symptoms were non-significant (g = 0.47, p = .387). These results are in line with previous research (Carl et al, 2019), but depict better outcomes than another meta-analysis (Fodor et al, 2018). Furthermore, our findings suggest that there is no significant difference between VRET and active controls regarding the improvement of PTSD symptoms (g = 0.25) and depressive symptoms (g = 0.24).…”
Section: Discussionsupporting
confidence: 92%
“…In sum, the evidence from the present metaanalysis was insufficient to assume efficacy of VRET for particular trauma types. While a considerable body of research supports the efficacy of VRET for the treatment of specific phobias (for an overview, see Carl et al, 2019;Fodor et al, 2018;Opriş et al, 2012), only a small number of controlled studies have investigated the efficacy of VRET in patients with PTSD. As such, we have to state that despite the moderately positive results of the present meta-analysis, more research is required to determine whether VRET constitutes a valuable tool for PTSD treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VRET is structured in a manner similar as traditional exposure therapy (1): via graded, systematic exposure to feared stimuli under controlled conditions and without safety behaviors, the fear response gradually habituates and inhibitory learning occurs (2). Since the first clinical applications of VR technology in the early 2000's, meta-analyses have revealed that VRET is efficacious (3), and even on par with traditional exposure therapy (4). Importantly, results generalize to reduced fear of real-world stimuli (5), there are low rates of deterioration (6) and efficacy has been demonstrated also among adolescents (7).…”
Section: Introductionmentioning
confidence: 99%